2019
DOI: 10.9734/bji/2019/v23i430083
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Characterization of Silver Nanoparticles from Ethanolic Extracts of Leaves of Annona muricata: A Green Nanobiotechnology Approach

Abstract: Introduction: The biological green synthesis of nanoparticles via nanobiotechnology processes have a significant potential to boost nanoparticles production without the use of harsh, toxic, and expensive chemicals commonly used in conventional physical and chemical processes. Annona muricata, a tropical plant belonging to family Annonaceae is one of the most used plants in folk medicine because of its many medicinal uses and therefore presents a strong candidate for use in green synthesis. Aims: The aim … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 51 publications
1
3
0
Order By: Relevance
“…The FTIR analysis in this study indicated the involvement of carboxyl, amino, amides groups and polyphenols in the synthesized green AgNPs. It is well known that there are amino acid, polyphenols, and protein in tea, the tea extract's organic compounds could assign to the reduction of AgNO3 and the stabilization of AgNPs by the surface bound by the organic compounds (41).This result was very close to Gavamukulya et al, (42). That included the functional groups responsible for AgNPs formation; alkenyl, alcohol groups, carboxylic acids, amides, and polyphenols.…”
Section: Fourier Transform Infrared Spectroscopy (Ftir)supporting
confidence: 80%
“…The FTIR analysis in this study indicated the involvement of carboxyl, amino, amides groups and polyphenols in the synthesized green AgNPs. It is well known that there are amino acid, polyphenols, and protein in tea, the tea extract's organic compounds could assign to the reduction of AgNO3 and the stabilization of AgNPs by the surface bound by the organic compounds (41).This result was very close to Gavamukulya et al, (42). That included the functional groups responsible for AgNPs formation; alkenyl, alcohol groups, carboxylic acids, amides, and polyphenols.…”
Section: Fourier Transform Infrared Spectroscopy (Ftir)supporting
confidence: 80%
“…The synthesis of AgNPs was performed using the green synthesis method that was previously prepared by Gavamukulya et al [30] after applying slight modifications. Aliquots of 9 mL of 2 mM silver nitrate were added to 1 mL A. muricata peel extract and following incubation for 8 h at RT, the bioreduction of AgNO 3 was achieved.…”
Section: Preparation Of Silver Nanoparticlesmentioning
confidence: 99%
“…Previously prepared and characterized AgNPs from ethanolic extracts of fruits (AgNPs-F) and leaves (AgNPs-L) of Annona muricata were used for the study [46][47][48]. AgNPs-F used had an absorption maximum at 427 nm and were stable under different pH, Temperature and storage conditions.…”
Section: Silver Nanoparticlesmentioning
confidence: 99%
“…To improve efficacy and bioavailability of plant derived medicinal products, green nanobiotechnology has been widely advocated for because of the various beneficial properties of nanosystems in delivery of bioactive components to target sites which conventional herbal treatments cannot meet [44,45]. In line with the above, this study employed previously green synthesized AgNPs from ethanolic extracts of fruits and leaves of Annona muricata [46][47][48] to study their anticancer activities on different cancer cell lines. It specifically involved exploring the in vitro anticancer activities of the AgNPs as well as studying their effects on expression of Caspase 9 (CASP9), C-X-C motif chemokine ligand 1(CXCL1) and C-X-C motif chemokine receptor 2 (CXCR2) genes in cervical and prostate cancer cell lines.…”
Section: Introductionmentioning
confidence: 99%